Correlation of Legal Concepts of Administrative Procedure and Administrative Liability in the Sphere of Urban Planning - Nataliia Zadyraka; Yevhen Leheza; Mykola Bykovskyi; Yevhenii Zheliezniak; Yulia Leheza (Jurnal Cita Hukum, 2023)
The purpose of the research is correlation of legal concepts of administrative procedure and administrative liability in the sphere of urban planning. Main content. The regulatory basis for imposition of administrative sanctions in the specified sphere consists in violation of legislation, building regulations, standards and rules, etc.  Methodology:  The methodological basis of the research is presented as comparative-legal and systematic analysis, formal-legal method, interpretation method, hermeneutic method as well as methods of analysis and synthesis. Conclusions. It is noted that the mechanism of bringing to administrative liability is based on a huge number of legislative acts, building codes, standards and rules, and this fact makes it much more difficult to understand this set of rules and contributes to their violation. Emphasis is placed on the fact that a large number of offenses in the sphere of urban planning activities are detected during state architectural and construction control and supervision. Disclosed are some positions of the Supreme Court regarding consideration and resolution of disputes related to appeal against resolutions on fine imposition. Peculiarities of implementation of norms of the institution of administrative liability in the sphere of urban planning activities for offenders of variable status have been revealed.Keywords: Administrative liability, administrative procedure, urban planning activity, legislation, urban planning offense